Retrospective assessment of metabolic syndrome components in early adult life on vegetarian dietary status - Pandya, Rachita; Abdelaal, Rashed; Chen, Joe W.; Masood, Shabana; Talib, Zohray; Atamna, Hani; Yakub, Mohsin; Hassan, Sherif S. (Frontiers in Public Health, 2022)
Background Metabolic syndrome (MetS) encompasses several clinical presentations that include truncal obesity and insulin resistance at its core. MetS afflicts 23% of the adult US population, increasing their risk of diabetes and cardiovascular disease. Many studies have indicated the importance of a vegetarian diet in improving overall health and more specifically MetS components. Unfortunately, these findings have been inconsistent and cannot be extended to examine effects on MetS incidence in the younger adult population. Objective This study aimed to conduct a retrospective analysis of a vegetarian vs. non-vegetarian dietary status in young adults (age 18–24) based on MetS components in later adulthood (age 20–30). This study focuses on elucidating any relationship between a vegetarian diet and MetS components of central obesity, hypertension, and hyperlipidemia. Methods: Waves 3 and 4 data were acquired from AddHealth. One-to-one propensity score matched vegetarians to non-vegetarians in a cohort of 535 women and 159 men. Logistical regression assessed the relationship between vegetarian status and MetS components, including truncal obesity (cm), hypertension (normal, pre-HT, HT1, and HT2), and hyperlipidemia (high and low). Results MetS components from ages 20 to 30 are not associated with vegetarian dietary status. Truncal obesity [N = 694; M = 92.82 cm; OR 0.999; p = 0.893; 95% CI (0.980, 1.017)]; hypertension [N = 694; OR 0.949; p = 0.638; 95% CI (0.764, 1.179)]; hyperlipidemia [N = 694; OR 0.840; p = 0.581; 95% CI (0.453, 1.559)]. Conclusion Current study results were consistent with previous findings suggesting that consumption of a vegetarian diet cannot be directly linked to MetS outcomes. However, further investigation should be completed as MetS is a risk factor for several chronic diseases.